(untitled) (Al-Aasar, 2025)
The digital transformation of news has shifted journalism from a profession anchored in verification and public service to one increasingly governed by metrics, platforms, and click-driven economics. While online distribution has expanded access and participation, it has also incentivized sensationalism, “clickbait” headlines, and algorithmic curation that can undermine trust. Drawing on scholarship on news credibility, audience analytics, and algorithmic gatekeeping, this conceptual paper examines how audience trust is being reshaped as journalism moves from credibility-centred norms to attention-centred logics. We synthesize literature on clickbait, metrics, and news trust to propose an integrative framework linking three layers: (1) newsroom practices driven by audience analytics and platform incentives, (2) platform architectures and algorithmic filtering, and (3) audience heuristics for evaluating credibility. We formulate research questions and propositions for future empirical work, with particular attention to the Global South where platform dependency and economic precarity intensify pressures toward clickbait and partisan content. The paper argues that trust in news is not simply eroding but being reallocated across legacy brands, digital-born outlets, influencers, and platforms. It concludes with normative and practical implications for rebuilding trust through transparency, slower news formats, audience engagement, and public-interest metrics that realign journalism with its core democratic functions.